Pengaruh Pengetahuan Gizi Ibu dan Asupan Balita terhadap Status Gizi Balita di Desa Ranto Panyang - Marbun, Wawa Marissa; Iskandar, Wardah; Ayunda, Hanif Muchdatul; Khairunnas, Khairunnas (Polyscopia, 2024)
This study investigates the relationship between mothers' nutritional knowledge, dietary intake of children, and under-five nutritional status in Ranto Panyang, Meureubo Sub-district, West Aceh. Despite varied economic conditions, malnutrition persists, highlighting the critical role of maternal knowledge in determining children's nutrition outcomes. Employing a cross-sectional quantitative design, this study surveyed mothers in 2023 to assess their understanding of nutrition and its effects on child health. Findings reveal that 52.4% of mothers possess adequate nutritional knowledge, while 47.6% demonstrate limited awareness. A statistically significant association (p<0.05) was identified between maternal knowledge and the nutritional status of under-fives, suggesting that improved maternal education could positively impact child nutrition. These results underscore the necessity of targeted educational initiatives, particularly in regions with high malnutrition rates, to empower mothers with essential nutrition knowledge and foster healthier communities.